2010
DOI: 10.1097/sla.0b013e3181d568db
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Deep Vein Thrombosis

Abstract: Factors associated with a higher rate of recurrence included unprovoked DVT and age >65. Elevated thrombus burden had a trend towards higher risk. Patients with surgery and trauma had low recurrence rates. Ipsilateral recurrence was strongly associated with PTS. PE occurred frequently and was a common cause of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 34 publications
1
14
0
3
Order By: Relevance
“…Some authors have reported a slightly increased risk (hazard ratio 1.36 per increase in each decade of age) (28,29), and others found no relationship (4,6,30), or even a decreased risk with ageing (31). In routine clinical practice, age at first venous thrombosis is usually taken into consideration when a patient is counseled regarding duration of anticoagulant treatment.…”
Section: Potential New Risk Factors For Venous Recurrencementioning
confidence: 99%
“…Some authors have reported a slightly increased risk (hazard ratio 1.36 per increase in each decade of age) (28,29), and others found no relationship (4,6,30), or even a decreased risk with ageing (31). In routine clinical practice, age at first venous thrombosis is usually taken into consideration when a patient is counseled regarding duration of anticoagulant treatment.…”
Section: Potential New Risk Factors For Venous Recurrencementioning
confidence: 99%
“…The cumulative incidence of recurrence was ≈ 16% after a mean followup of 1216 days from the initial VTE event in the patients included in the Worcester VTE study [19]. An incidence of recurrence of 26.1% at 5 years was recorded in a small series of patients with DVT by Labropoulos et al [20]. Poli et al [21] have prospectively followed a series of 206 patients with acute PE.…”
Section: Incidence Of Vte Recurrencementioning
confidence: 99%
“…Obrzęk i ból go le ni są naj bar dziej ty po wy mi, wcze sny mi ob ja wami roz wi ja ją cej się za krze pi cy żyl nej. Niele czo na ostra za krze pi ca żył głę bo kich pro wa dzi w 33-50% do zato ro wo ści płuc nej [2,[3][4][5][6].…”
Section: Wstępunclassified
“…The most typical early manife stations of a developing venous thrombosis include oedema and tibial pain. Uncontrolled acute deep vein thrombosis leads to pulmonary embolism in 33-50% of patients [2,[3][4][5][6].…”
Section: Wy Tycz Ne Mię Dzy Na Ro Do We I Pol Skie Pro Fi Lak Ty Ki Vtementioning
confidence: 99%
See 1 more Smart Citation